Purification and Components Identification on Spinach (Amaranthus sp. L.) and Broccoli (Brassica oleracea L.) Fermented by Kombucha Culture as Source of Folic Acid Through Stirred Microfiltration Cell (SMFC) - Agustine Susilowati; Aspiyanto Aspiyanto; Puspa D. Lotulung; Hakiki Melanie; Yati M (Institut Teknologi Sepuluh Nopember, 2017)
Purifying spinach (Amaranthus sp.) and broccoli (Brassica oleracea L.) fermented by Kombucha culture through microfiltration (MF) membrane of 0.15 µm fitted in Stirred Microfiltration Cell (SMFC) produced subsequently both fermented spinach and broccoli concentrates with compositions of folic acid of 58.9 µg/mL and 28.1 µg/mL, total solids of 6.29 % and 5.76 %, total acids of 0.57 % and 0.93 %, polyphenol of 0.25 % and 0.06 %, and reducing sugars of 105.34 mg/mL and 66.09 mg/mL. In these conditions, recovery of both fermented spinach and broccoli concentrates mentioned above were 1.07 times and 0.64 times, 0.95 times and 0.97 times, 1 times and 1 times, 3.57 times and 0.85 times, 1.22 times and 0.68 times compared to feed, Based on both the best molecular weight (MW) and relative intensity, dominant monomer was reached for fermented spinach extract and gave folic acid fractionation, folic acid and polyphenol with MW of 219.57 Dalton (Da.), 442.99 Da. and 192.11 Da., and relative intensities of 19.78 %, 0.81 % and 1.65 %, respectively.